PENGARUH INVOLVEMENT, FAMILIARITY,BRAND LOYALTY, DAN PRICE SENSITIVITY TERHADAP KEPUTUSAN PEMBELIAN PRODUK SUSU BUBUK MEREK DANCOW DI SURABAYA SELATAN (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2011)
This study entitled "Effect of Involvement, Familiarity, Brand Loyalty, Price Sensitivity and Product Purchasing Decision Against Brand Milk Powder Dancow in South Surabaya. The main purpose of this study was to examine the effect of involvement, familiarity, brand loyalty and price sensitivity in decision making. Data was collected using a survey questionnaire distribution to 100 respondents, but only 77 questionnaire swhich can be further investigated. Research using primary data from 100 respondents. The sampling technique used in this study was purposive sampling. Using multiple linear regression analysis using SPSS version 16. The respondents of this research are people who buy milk powder Dancow from Nestle for their children. The results showed that there was a significant influence of brand loyalty on Purchase Decision Making Powdered Milk Products Brand Dancow in South Surabaya. The results also show that involvement, familiarity, price sensitivity has no effect on Decision Making. Brand Loyalty significantly influence decisions simultaneously and in part for people to buy milk powder Dancow. Based on the analysis in this study obtained evidence that is obtained by calculating the F value that is equal to 3.282 which is greater than the F table is 2.4989 which means that the independent variable consisting of Involvement (X1), Familiarity (X2), Brand Loyalty (X3), Price Sensitivity (X4) simultaneously has a significant influence on purchase decisions (Y), and based on the t value obtained from each of the variables, namely Involvement (X1)=-0.125, Familiarity (X2) =-0.042, Brand Loyalty (X3) =3.00, and Price Sensitivity (X4) =0.152. While the tablet value 1.9935. t count of Brand Loyalty is bigger than t table value, while t count of Involvement variable (X1), Familiarity (X2), and Price Sensitivity (X4) is smaller than t table. So it canbe said that the only variable is the partial Brand had an influence on purchase decisions. Variable Brand Loyalty (X3) is a variable that has a dominant influence on purchase decisions because of the partial coefficient of determination (r2) Brand Loyalty variable (X3) of 0.089401 is greater than the value of the partial coefficient of determination (r2) the other independent variables.